Contemporary rates of pathological features and mortality for adenocarcinoma of the urinary bladder in the USA. (22nd November 2016) - Zaffuto, Emanuele; Gazdovich, Stéphanie; Leyh‐Bannurah, Sami‐Ramzi; Huland, Hartwig; Abdollah, Firas; Shariat, Shahrokh F; Menon, Mani; Briganti, Alberto; Montorsi, Francesco; Karakiewicz, Pierre I
Abstract : Objectives: To examine contemporary rates of pathological features and mortality for adenocarcinoma of the urinary bladder in the USA using population‐based data analysis. Methods: We relied on 10 024 patients with non‐metastatic bladder cancer diagnosed between 2004 and 2013 within the Surveillance, Epidemiology and End Results registries. Logistic regression analyses focused on grade and stage. Kaplan–Meier analyses assessed cancer‐specific mortality rates in adenocarcinoma and urothelial carcinoma of the bladder. Cox regression analyses assessed the impact of histological subtype on cancer‐specific mortality. Results: Overall, 215 (2.1%) adenocarcinoma and 9809 (97.9%) urothelial carcinoma patients were identified. The rate of non‐organ‐confined disease was higher in adenocarcinoma (64.7% vs 50.8%, P < 0.001). In multivariable logistic regression analyses, adenocarcinoma patients had a 2.2‐fold higher risk of harboring non‐organ‐confined disease (95% confidence interval 1.7–3.0; P < 0.001) than urothelial carcinoma patients. Cancer‐specific mortality‐free survival rates were lower in adenocarcinoma ( P < 0.01). This disadvantage only applied to non‐organ‐confined disease ( P = 0.044), and not to organ‐confined disease ( P = 0.9). In multivariable Cox regression analyses, adenocarcinoma conferred a 1.3‐fold higher rate of cancer‐specific mortality (hazard ratio 1.30, 95% confidence interval 1.05–1.60; P = 0.01). Among adenocarcinoma patients, 30.7% harbored signet‐ring cell adenocarcinoma and portended particularly poor cancer‐specific mortality rates. Conclusions: In bladder cancer, adenocarcinoma presents at higher stages than urothelial carcinoma. However, cancer‐specific mortality rates do not differ. A more unfavorable stage at diagnosis and higher cancer‐specific mortality apply to the signet‐ring cell variant.